2019
DOI: 10.2172/1526619
|View full text |Cite
|
Sign up to set email alerts
|

Development of Heat Pipe Reactor Modeling in SAM

Abstract: System Analysis Module (SAM) is under development at Argonne National Laboratory as a modern system-level modeling and simulation tool for advanced non-light water reactor safety analyses. It utilizes the object-oriented application framework MOOSE to leverage the modern software environment and advanced numerical methods available in PETSc. The capabilities of SAM are being extended to enable the transient modeling, analysis, and design of various advanced nuclear reactor systems. This report presents the dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 6 publications
0
13
0
1
Order By: Relevance
“…A more detailed heat structure temperature distribution is given in Figure 12, from which it can be observed that the largest temperature gradients are in the wall and wick region of both evaporator and condenser sections, while the vapor core temperature is almost constant. More details on heat pipe simulation capability of SAM and its application in modeling heat pipe cooled reactors could be found in [11] and [12].…”
Section: D Heat Structure and 3d Porous Medium Flow Couplingmentioning
confidence: 99%
“…A more detailed heat structure temperature distribution is given in Figure 12, from which it can be observed that the largest temperature gradients are in the wall and wick region of both evaporator and condenser sections, while the vapor core temperature is almost constant. More details on heat pipe simulation capability of SAM and its application in modeling heat pipe cooled reactors could be found in [11] and [12].…”
Section: D Heat Structure and 3d Porous Medium Flow Couplingmentioning
confidence: 99%
“…The VHTM technology is expected to lead to slightly reduced heat removal capability in the evaporator region due to smaller heat conduction properties of hydride metal in the wick when compared to conventional wick technology. Using the System Analysis Module (SAM) code for simple heat pipe modeling [15], the heat removal performance of a VHTM was found to be ~20% lower when compared with conventional design. However, this slightly negative impact on heat transfer performance should easily be compensated by design changes on the heat pipe facilitated by the reduced neutronic penalty obtained.…”
Section: Preliminary Demonstration Of Technology Benefitsmentioning
confidence: 99%
“…The System Analysis Module (SAM) [1,2,3,4] is an advanced system analysis tool being developed at Argonne National Laboratory under the U.S. Department of Energy (DOE) Nuclear Energy Advanced Modeling and Simulation (NEAMS) program. It aims to be a modern system analysis code, which takes advantage of the advancements software design, numerical methods, and physical models over the past two decades.…”
Section: Sam Overviewmentioning
confidence: 99%